Lean Management’s Effect on Industry 4.0 Regarding Innovation - Serkan Naktiyok; Mehmet Burhanettin Coşkun; Fatma Temelli (Istanbul Business Research)
This study intends to investigate the relationship between lean management, Industry 4.0, and innovation perceptions in employees of companies in Turkey’s general tourism sector and to determine whether these perceptions have an impact on how lean management influences perceptions of Industry 4.0. Businesses are compelled to participate in innovation activities due to the fourth industrial revolution, or industry 4.0, which is characterised by the rapid advancement and change of technology. On the other hand, there is a dearth of empirical research on the impact of lean management practises in enterprises on innovation and industry 4.0. Thus, by examining the connection between lean management, industry 4.0, and the innovation process as well as the impact of lean management on these three elements, the study seeks to advance the area. The sample consists of 527 employees in employment in the tourism sector (hotels, agencies). Surveys were used to gather data, which structural equivalency modelling was used to assess. According to the study’s findings, lean management has a favourable impact on innovation and industry 4.0. Another finding is that innovation affects Industry 4.0. The emergence of new and creative ideas in businesses will lead to the creation or development of advanced production technologies. The principal discovery of the study indicates that innovation functions as a mediator in the correlation between industry 4.0 and lean management.